Traditional authorities in Africa : resurgence in an Era of democratisation - Ubink, Janine M., 1976- (Law, governance, and development. Research., 2008)
Traditional authority is a distinguishing feature in the landscape of contemporary Africa. It remains important in organising the life of the people at the local level despite modern state structures. And since the 1990s, African governments, international institutions and donor organisations have shown a renewed interest in it. As a result, a large number of African countries have enhanced or formalised the position of their chiefs. At the same time, however, this resurgence of traditional authority coincides with the wave of democratisation across sub- Saharan Africa, and many question the desirability and legitimacy of traditional authority in modern forms of governance. This title can be previewed in Google Books - http://books.google.com/books?vid=ISBN9789087280529.